The Optimalisasi Pemberdayaan Pengajar: Dampak Motivasi Kerja, Kompetensi Profesional, dan Budaya Organisasi terhadap Efikasi Diri Guru - Paramudita Chintya Putri; Lia Yuliana (Postgraduate, University of Mataram, 2024)
This study aims to determine the effect of work motivation, teacher professional competence, and organizational culture on teacher self-efficacy at MTS Asy Syaafi`Iyyah and SMP PGRI 1 Kuwarasan after the Covid-19 pandemic. This type of research is ex-post facto with a quantitative approach. The study population was 38 teachers at MTS Asy Syaafi`Iyyah and SMP PGRI 1 Kuwarasan. Determination of the research sample of 35 teachers using simple random sampling technique. Instrument validation using expert judgment and empirical test with Pearson Product Moment correlation. Instrument reliability test was conducted with Cronbach's Alpha. The analysis requirements test was carried out by testing normality, linearity, and multicollinearity. Simple linear regression was performed as data analysis to test the effect of each independent variable (1, 2, 3) on the dependent variable (Y) and multiple linear regression was performed as data analysis to test the effect of independent variables (1, 2, 3) simultaneously on the dependent variable (Y). The results showed that: there is a positive and significant influence between work motivation on teacher self efficacy of 31.70% with a value of t = 4.08 and Sig = 0.000; there is a positive and significant influence between teacher professional competence on teacher self efficacy of 42.70% with a value of t = 5.183 and Sig = 0.000; there is a positive and significant influence between teacher professional competence on teacher self efficacy by 42.50% with a value of t = 5.158 and Sig = 0.000; and there is a simultaneous positive and significant influence between work motivation, teacher professional competence, and organizational culture on teacher self efficacy by 54% with a value of F = 13306 and Sig = 0.000).